OPTIMAL IRRIGATION REGIMES FOR ULTRA-EARLY MATURING WINTER WHEAT VARIETIES - Durdiyev, N.H.; Gʻopporova, Z.I. (Research Focus International Scientific Journal, 2026)
This article presents the results of research conducted on ultra-early maturing winter wheat varieties, where pre-irrigation soil moisture was maintained at 70–70–65%, 75–75– 70%, and 80–80–75% relative to field capacity (FC).